2021
DOI: 10.1177/03915603211007030
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and oncological outcomes of renal cell carcinoma with venous tumour thrombus

Abstract: Aim: The aim of the present study is to report the perioperative and long-term surgical outcomes of renal cell carcinoma (RCC) with venous tumour thrombus (VTT). Materials and methods: Data of 34 patients (males = 23, females = 11) from 2009 to 2020 who underwent radical nephrectomy with thrombectomy for RCC and VTT was retrospectively analysed. The parameters recorded include tumour laterality, size, level of thrombus, surgical approach, blood loss, transfusion rates, operative time, hospital stay, Clavien co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…VTT was con rmed to have signi cant in uence on the prognosis of RCC patients [29][30][31][32]. In the study of Blute et al…”
Section: Baseline Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…VTT was con rmed to have signi cant in uence on the prognosis of RCC patients [29][30][31][32]. In the study of Blute et al…”
Section: Baseline Characteristicsmentioning
confidence: 97%
“…It reveals that patients with higher tumor thrombus level would have more possibility to get early postoperative complications including renal insu ciency. So more accurate preoperative assessment of the thrombus extent and location is crucial in achieving optimal surgical outcomes in patients of RCC with VTT, particularly with higher level (level and ) thrombus [31]. Furthermore, Ebbing et al [24] found that the main risk factor for severe early postoperative complications in the univariate (OR, 16.421; 95% CI, 2.117-127.359; P=0.007) and multivariate (OR, 11.847; 95% CI, 1.469-95.560; P=0.020) analyses was supradiaphragmatic tumor thrombus (level tumor thrombus).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Most cases of RCC grow by expansion and can often extend into the renal pelvis, causing focal hydronephrosis or displacement of the caliceal. In contrast to TCC, RCC has a tendency to spread into the venous system [12].…”
Section: Rccmentioning
confidence: 99%